2011
DOI: 10.1038/aps.2011.18
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of insulin receptor substrate 2 reverses oncogenic transformation induced by v-src

Abstract: Aim: To investigate the role of insulin receptor substrate 2 (IRS-2) in oncogenic transformation induced by v-src. Methods: IRS-2 gene was silenced using small interfering RNAs (siRNAs). Nuclear translocation and interaction of IRS-2 with v-src was determined using subcellular fractionation, confocal microscopy, and immunoprecipitation. The activity of the cyclin D1 promoter and r-DNA promoter was measured with a luciferase assay. Results: Depletion of IRS-2 inhibited R-/v-src cell growth and reverse the oncog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Most of these studies suggest that Src function is required in the upstream part of the signaling pathway - in some contexts, Src associates with and/or is activated by the ligand-bound receptor 8 9 10 11 12 . Intersections of Src signaling with the insulin/IGF pathway have also been described at the level of insulin receptor substrate (IRS) proteins 13 14 , phosphoinositide 3-kinase (PI3K) 15 and in the activation of AKT 16 17 18 19 . The main limitation of these biochemical studies is that they are mostly based on experiments in cell culture and often employ tools like the rather unspecific Src inhibitors PP1 and PP2, and therefore it is difficult to deduce the relevance of Src signaling in actual in vivo conditions in the living organism from them.…”
mentioning
confidence: 99%
“…Most of these studies suggest that Src function is required in the upstream part of the signaling pathway - in some contexts, Src associates with and/or is activated by the ligand-bound receptor 8 9 10 11 12 . Intersections of Src signaling with the insulin/IGF pathway have also been described at the level of insulin receptor substrate (IRS) proteins 13 14 , phosphoinositide 3-kinase (PI3K) 15 and in the activation of AKT 16 17 18 19 . The main limitation of these biochemical studies is that they are mostly based on experiments in cell culture and often employ tools like the rather unspecific Src inhibitors PP1 and PP2, and therefore it is difficult to deduce the relevance of Src signaling in actual in vivo conditions in the living organism from them.…”
mentioning
confidence: 99%
“…The Stat3 signaling pathway has been shown to interact with the PI3K-AKT-mTOR, MAPK, and p38 pathways 20 , 42 , 43 , 44 , 45 , 46 ( Figure 4a ). Therefore, we examined the effects of tanshinone-1 on the key signaling molecules, AKT, ERK, and p38, of these pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression or activation of Src is frequently detected in a variety of tumors [17,19]. It has been reported that IRS2 depletion can reverse oncogenic transformation induced by Src [22], suggesting that IRS2 is a key effector downstream of Src. Our work reveals that AFB1 can induce Src phosphorylation and stabilize IRS2.…”
Section: Discussionmentioning
confidence: 99%
“…Under hypoxic conditions, Src activation leads to overexpression of vascular endothelial growth factor (VEGF), matrix metalloproteinases (MMP), and interleukin-8, which in turn stimulate tumor angiogenesis and metastasis [14,19,20]. Src interacts with both IRS1 and IRS2, which have critical roles in cell growth, migration, and metabolism [21,22]. IRS1/2 relay signaling through insulin receptor and IGF-1R by recruiting many Src homology 2 (SH2) domain-containing proteins [23,24].…”
Section: Introductionmentioning
confidence: 99%